2018
DOI: 10.1111/joca.12180
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review to Identify Successful Elements for Financial Education and Counseling in Groups

Abstract: This study reviews the literature available on contents, form, and effectiveness of group‐based programs for combined financial education and counseling aimed specifically at populations at risk for financial difficulties. Despite the widespread application of these programs, relatively little is known about their effectiveness. In general, evidence points to positive effects of several programs on knowledge, confidence, and (intended) behavior, but the exact mechanisms through which this is achieved remain un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 69 publications
1
44
0
2
Order By: Relevance
“…Hence, sustainable financial education is important and positive for improving consumer life satisfaction in the long-term. According to Peeters et al [52], prior knowledge and intended behavior, namely, having accepted financial education and considering the necessity of financial education in this study, had positive effects on sustaining financial knowledge. In addition to the subjective measure of sustainable financial education, this paper proposes the two following hypotheses: Hypothesis 1 (H1).…”
Section: The Impact Of Sustainable Financial Education and Consumer Lmentioning
confidence: 57%
See 1 more Smart Citation
“…Hence, sustainable financial education is important and positive for improving consumer life satisfaction in the long-term. According to Peeters et al [52], prior knowledge and intended behavior, namely, having accepted financial education and considering the necessity of financial education in this study, had positive effects on sustaining financial knowledge. In addition to the subjective measure of sustainable financial education, this paper proposes the two following hypotheses: Hypothesis 1 (H1).…”
Section: The Impact Of Sustainable Financial Education and Consumer Lmentioning
confidence: 57%
“…Atkinson et al [54] also indicated that financial education can improve the level of consumer financial literacy and encourage consumers to conduct rational financial behavior, thereby improving consumers' financial ability and improving their life satisfaction. It is evident that the changes in financial behaviors require a period of time, and programs involving financial education may cause an increase in training costs [52]. From the objective perspectives of measuring sustainable financial education, this implies that the higher the financial education level of consumers, the more money and time they spend on sustainable financial education after their formal schooling is complete, and the higher their life satisfaction is.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
“…Such research has implications for several financial behaviors such as saving (Soman and Zhao ; Ülkümen and Cheema ), and managing one's finances (Ameriks, Caplin, and Leahy )—behaviors that are typically conceptually characterized as entailing longer‐term goal‐directed behavior. Financial self‐efficacy, similarly, is known to mediate the relationship of financial literacy—another key risk factor for financial vulnerability—with financial outcomes (Fernandes, Lynch, and Netemeyer ; Peeters et al ; Perry and Morris ). Together, the above research invites the suggestion that consumers facing difficult financial circumstances may experience psychological, as well as financial consequences.…”
mentioning
confidence: 99%
“…The TPB guides existing scholarship regarding individual fiscal management of cash, credit, or savings (Xiao, 2008). Attitude is the strongest predictor of financial behavior intention, whereas the effect of subjective norms (i.e., behavioral expectation) on intention is inconclusive (Peeters et al, 2018). The subjective Figure 1.…”
Section: Theoretical Frameworkmentioning
confidence: 99%